From Physical to Digital: What does IoT mean for economic growth? - Harry Fernando Aquije Ballon; Kalvin Bahia; Pau Castells (International Telecommunications Society (ITS), 2024)
While mobile technologies have already connected billions of people, the Internet of Things (IoT) is now adding all kinds of devices to the digital ecosystem. The potential benefits of connecting the physical world to the internet are vast, but not well understood. This study provides a contribution to quantify the contribution of IoT to economic growth. By leveraging a unique dataset that measures IoT connections by vertical industry across 163 countries between 2010 and 2022, we find that IoT made a significant contribution to GDP growth. On average, a 10 percentage point increase in IoT connections per inhabitant increased GDP by 0.7% in LMICs and 0.5% in HICs. We find that this impact is primarily driven by enterprise IoT, accounting for 80% of the total effect, while consumer IoT contributed 20%.
Keywords: O47; O33; L96; O11; O4; 330